POSTPARTUM DIASTASIS SYMPHYSIS PUBIC: A CASE STUDY - Sudarmi, S; Wahyuni, W (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Pubic symphysis diastasis is the weakness of the ligaments in the pubis that causes the separation of the pubic bone due to hormonal or normal delivery of a baby that is too large (Naoum, & Garner, 2003). Incidence of cases like this is rare but as reported prevalence in a year can reach 520 to 20,000 per case. Case Presentation: A 25-year-old woman has achieved HPL and delivered normally or spontaneously, then the patient was diagnosed with Diastasis Symphysis Pubis with a distance of 3.42 cm. Management and Outcome: The management is in the form of Tens,mobilization exercises, pain reduction and pelvic floor exercises to reduce the level and intensity of pain, increase muscle strength and increase joint range of motion and restore functional ability. Discussion: pubic symphysis instability can lead to joint inflammation, leading to difficulties in outpatient care. Severe dilation of the pubic symphysis damages the ligaments associated with the bones of the bones. If the distance between the symphysis pubis is greater than 2 cm on radiographs, involvement of the sacroiliac joints is often seen. In our research, almost half (16/33, 48.5%) of patients with PPSD had a pubic symphysis dilation of more than 2 cm according to (Sung et al., 2021), in this case study the patient had a pubic width of 3.42 Cm but after doing a physiotherapy program 2 times a week at the hospital for 3 days and doing the exercises at home to get results for approximately 3 months decreased to 1.85 Cm. Conclusion: handling of Physiotherapy programs given to patients 2 times a day for mobilization exercises and pelvic floor exercises in order to prevent joint stiffness and decrease in abdominal and pelvic muscle strength.